The Education and Training Program Guideline for Special Guidance Teacher Competence Development in Indonesian Inclusive School - Ediyanto, Ediyanto; Mulyadi, Agus; Supriatna, Agus; Kawai, Norimune (The Center for Disability Studies and Services Brawijaya University, 2018)
The provision of inclusive schools in Indonesia requires the fulfillment of several aspects of Inclusive Education. The fulfillment of these needs includes curriculum, facilities and infrastructure, teachers, and learning in accordance with the principles of Inclusive Education. Teachers in inclusive classes must have the competence to teach students with special needs. In addition, inclusive classes also require Special Guidance Teachers as an instructional design or as a team teaching. However, the training program for Special Guidance Teachers has not been developed in a general, comprehensive, and integrated manner. So that in this article an education and training program was developed for the teacher competence development guidelines in Indonesian inclusive school. If every school requires at least one Special Guidance Teacher, then at the elementary formal education level, junior high, high school and equivalent schools, the total number of Special Guidance Teachers is 259,244 teachers. While for the kindergarten level the number of teachers is 85,499 teachers. Competency Standards for Special Guidance Teachers refer to Minister of National Education Regulation No. 16 of 2007 - Academic Qualification Standards and Competencies of Teachers and Minister of National Education Number 32 of 2008 - Academic Qualification Standards and Competencies of Special Education Teachers. In general, there are four competencies that must be mastered by Special Guidance Teachers, namely Personality, Social, Pedagogic, and Professional Standards. The title of this program is “The Education and Training Program Guideline for Special Guidance Teacher Competence Development. This prorgam divided into three main subjects, namely general training subjects, basic training subjects, and supporting training subjects with the number 47 subject and 450 hours. This program has not been validated and field tested yet. In the next research step it is necessary to validate it by experts and to do field test to determine the level of validity and effectiveness of the program.